Novel terpolymers based on methyl methacrylate with superior thermal stability and optical transparency for high-value applications - Shahrzad Jahangiri; Ladan Gramifar (PLoS ONE, 2025)
Methyl methacrylate (MMA) is a widely utilized polymer in high-value applications; however, it faces limitations due to its inherent thermal instability and moderate optical transparency. This study addresses these challenges by reporting the successful synthesis of novel terpolymers comprising MMA, 4-vinylbenzyl chloride (VBC), and N-2-methyl-4-nitrophenyl maleimide (MI) through radical solution polymerization. The incorporation of these co-monomers, particularly at optimized molar ratios (e.g., MMA/VBC/MI of 40:30:30), significantly enhances the performance of the polymer. The synthesized terpolymers underwent extensive characterization utilizing FTIR, NMR, CHNS, TGA, DSC, and UV-Vis spectroscopy, in addition to solubility and viscosity analyses. Our results indicate significant advancements in thermophysical and optical properties. Specifically, the terpolymers exhibited markedly improved thermal stability, with the P(MMA40-VBC30-MI30) sample demonstrating the highest decomposition temperature (T10) of 319°C, a substantial increase from PMMA’s T10 of 221°C. The glass transition temperature (Tg) was also significantly enhanced, reaching 119°C across all terpolymer compositions, surpassing PMMA’s Tg of 104°C. Furthermore, these innovative terpolymers achieved exceptional optical clarity. While P(MMA60-VBC10-MI30) displayed 98% light transmission, the optimized compositions, P(MMA50-VBC20-MI30) and P(MMA40-VBC30-MI30), remarkably reached 100% light transmission across the visible spectrum (400−800 nm), considerably exceeding PMMA’s 90% transmission. This high transparency, even with the incorporation of the chromophoric maleimide unit, underscores a synergistic effect of VBC in reducing transparency loss. Additionally, the terpolymers demonstrated improved solubility in common solvents and reduced intrinsic viscosity (0.19–0.38 dL/g compared to PMMA’s 0.86 dL/g), indicating enhanced processability. Despite the observed partial incorporation of MI (approximately 50% as determined by CHNS analysis), these methyl methacrylate-based terpolymers signify a significant advancement, providing co-optimized thermal stability, optical transparency, and enhanced processability. Their multifunctional properties render them highly promising candidates for demanding applications, particularly within the aerospace industry, where high performance, thermal resistance, and visual clarity are essential.